Modeling and characterization of optimal nano-scale channel dimensions for fin field effect transistor based on constituent semiconductor materials - Waheb A. Jabbara; Ahmed Mahmood; Jamil Sultan (Universitas Ahmad Dahlan, 2022)
This study aims to design an optimal nano-dimensional channel of fin field effect transistor (FinFET) on the basis of electrical characteristics and constituent semiconductor materials (Si, GaAs, Ge, and InAs) to overcome issues regarding the shrinking of dimensions and ensure the best performance of FinFETs. This objective has been achieved by proposing a new scaling factor, K, to simultaneously shrink the physical scaling limits of channel dimensions for various FinFETs without degrading their performance. A simulation-based comprehensive comparative study depending on four variable parameters (length, width, oxide thickness of the channel, and scaling factor) was carried out. The influence of changing channel dimensions on the performance of each type of FinFET was evaluated according to four electrical characteristics: i) ON-state/OFF-state current (ION/IOFF) ratio, ii) subthreshold swing (SS), iii) threshold voltage, and iv) drain-induced barrier lowering. The well-known multi-gate field-effect transistor (MuGFET) simulation tool for nanoscale MuGFET structure was utilized to conduct experimental simulations under the considered conditions. The obtained simulation results showed that the optimal channel dimensions for the best performance of all considered FinFET types were achieved at a minimal scaling factor K=0.125 with 5 nm length, 2.5 nm width, and 0.625 nm oxide thickness of the channel.